Varicose vein surgery under anti-platelet therapy - Miszczak, Z. T.; Baier, P.-M. (Phlebologie, 2008)
Background: Platelet function inhibitors (PFI) are used for prophylaxis of atherothrombosis. These drugs cause a prolongation of the bleeding time and should eventually be stopped before an elective operation. However, there is a risk that a perioperative pause of PFI lead to acute atherothrombosis. Objective: Our aim was to study whether a discontinuation of PFI therapy is necessary to avoid bleeding complications in patients undergoing varicose vein surgery. Methods: Selective review of the literature and retrospective analysis of clinical data of our own patients. Results: In the years 2002 to 2007 a total of 10 827 patients have been operated on varicose veins, 673 (6.2%) of these aged 32–86 years (67 ± 7.9) receiving permanent PFI therapy: 256 male patients (38.0%) and 417 female (62.0%), 39.1% categorized as ASA III patients: male 11.6%, female 27.5%. 38 patients who continued PFI therapy did not demonstrate haemorrhagic complications and none of those pausing anti-platelet medication experienced thromboembolic complications. The literature survey confirmed our finding that it is not necessary to suspend PFI medication for varicose vein surgery as the bleeding risk can be controlled for by technical means. Conclusion: Discontinuation of PFI therapy prior to interventions on varicose veins does not seem to be necessary, further studies are essential though.
Keywords: Platelet function inhibitors; varicose vein surgery; haemorrhagic complications